2016
DOI: 10.5539/elt.v9n6p229
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Blended Learning Writing Environment: Effects on EFL Students’ Writing Apprehension and Writing Performance

Abstract: This study examined the effects of collaborative blended learning writing environment on students' writing apprehension and writing performance as perceived by a selected group of EFL students enrolled in one of the international schools in Malaysia. Qualitative case study method was employed using semi-structured interview, learning diaries and observation. Twelve male students enrolled in Class Ten were selected to participate in a 13-week study. To learn how to write collaboratively, the students followed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Collaborative learning is also believed to help learners improve their writing skills effectively (Challob et al, 2016;Pratiwi, 2020;Rizki et al, 2020;Supiani, 2012). Supiani (2012) has demonstrated results of his study that collaborative learning is beneficial to help learners improve their learners' writing competence, behavior, motivation, and class situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative learning is also believed to help learners improve their writing skills effectively (Challob et al, 2016;Pratiwi, 2020;Rizki et al, 2020;Supiani, 2012). Supiani (2012) has demonstrated results of his study that collaborative learning is beneficial to help learners improve their learners' writing competence, behavior, motivation, and class situation.…”
Section: Discussionmentioning
confidence: 99%
“…Supiani (2012) has demonstrated results of his study that collaborative learning is beneficial to help learners improve their learners' writing competence, behavior, motivation, and class situation. Other fruitful benefits of collaborative learning techniques are improving learners' selfconfidence and active participation (Pratiwi, 2020), reducing writing apprehension (Challob et al, 2016), as well as enhancing learners' writing ability in composing a text (Rizki et al, 2020). These results of studies have implied that the use of collaborative learning techniques can be used as solutions in solving problems related to the use of grammatical cohesion in writing.…”
Section: Discussionmentioning
confidence: 99%
“…While the line of research on instructional materials acknowledges the importance of reading material as an important channel for developing a knowledge repertoire, it particularly points out the limited content in traditional textbooks, and suggests the potential of using online resources to supplement in-classroom teaching because of its easy accessibility and multimodal learning platform (Lau et al, 2018;Taffs & Holt, 2013;Tomlinson, 2003). Unfortunately, the use of online resources for writing instruction is still clustered around teaching vocabulary (e.g., Gilmore, 2008), nurturing students' ideas for academic writing topics (e.g., Sloan, Porter, Robins, & McCourt, 2014), creating collaborative learning platforms, such as online bulletin boards (e.g., Challob, Bakar, & Latif, 2016;Ferriman, 2013), or writing structure (Taffs & Holt, 2013). In other words, these studies on the relationship between online resources and writing are limited to the macro landscape of e-learning resources as regards writing.…”
Section: Teaching Based On Online Resourcesmentioning
confidence: 99%
“…The use of this academic resource strengthens students' writing performance tasks. Challob, Bakar, and Latif (2016) found that this process advocates group work raises students' understanding of their strengths and weaknesses and creates shared learning. Wang and Chen (2013) considered that some of the advantages of collaboration are the development of shared knowledge, understanding, and participation.…”
Section: Collaboration In Writingmentioning
confidence: 99%